Mechanism research and treatment progress of NAD pathway related molecules in tumor immune microenvironment - Xu, QinChen; Liu, Xiaoyan; Mohseni, Ghazal; Hao, Xiaodong; Ren, Yidan; Xu, Yiwei; Gao, Huiru; Wang, Qin; Wang, Yunshan (Cancer cell international, 2022)
Nicotinamide adenine dinucleotide (NAD) is the core of cellular energy metabolism. NAMPT, Sirtuins, PARP, CD38, and other molecules in this classic metabolic pathway affect many key cellular functions and are closely related to the occurrence and development of many diseases. In recent years, several studies have found that these molecules can regulate cell energy metabolism, promote the release of related cytokines, induce the expression of neoantigens, change the tumor immune microenvironment (TIME), and then play an anticancer role. Drugs targeting these molecules are under development or approved for clinical use. Although there are some side effects and drug resistance, the discovery of novel drugs, the development of combination therapies, and the application of new technologies provide solutions to these challenges and improve efficacy. This review presents the mechanisms of action of NAD  pathway-related molecules in tumor immunity, advances in drug research, combination therapies, and some new technology-related therapies.